Short-term aerobic exercise does not change kidney function in students of Nnamdi Azikiwe University, Nigeria - Chinedu, Ihim Augustine; Obi, Patrick Chinedu; Udoka, Egbe Josephat; Osakue, Nosakhare; Ozuruoke, Donatus F.; Nwobodo, Emmanuel I.; Meludu, Samuel C.; Okechukwu, Okeke Chizoba (Faculty of Medicine, Trisakti University, 2017)
BackgroundExercise has been known to have beneficial effects on human health. The kidneys play an important role in regulating acid-base and water-electrolyte balance disturbances induced by exercise. The objective of this study was to investigate the effect of short term aerobic exercise (volleyball training) on the kidney function of apparently healthy individuals. MethodsAn experimental study of pre-post test design was conducted involving 41 amateur volleyball players, comprising 22 males and 19 females. They were randomly divided into seven different teams. Each team trained for at least 45 minutes for four consecutive days for two weeks. Both pre-and post-exercise blood pressure (BP) was measured using an automatic blood pressure measuring device OMRON 907 (OMRON, Hoofddorp, Netherlands). Likewise, both pre- and post-exercise blood samples were collected into lithium heparin tubes and centrifuged at 3000 rpm for 10 minutes and the plasma separated into plain tubes. Electrolytes were analysed using ion selective electrode machine (SFRI 4000, Germany), urea using modified Berthelot method, creatinine using Jaffe-Slot method and uric acid using the uricase method and estimated glomerular filtration state (eGFR) was calculated using the Modification of Diet in Renal Disease (MDRD) formula. ResultsThe mean levels of pre- and post-exercise systolic blood pressure, creatinine, urea, sodium, potassium, chloride, bicarbonate and eGFR did not differ significantly (p>0.05). However, serum uric acid was significantly increased (p<0.05), while diastolic BP significantly decreased after exercise (p<0.05).ConclusionThe study showed that short-term moderate intensity aerobic exercise does not have any significant effect on the renal functions.